Digital Watermarking Method Warranting the Lower Limit of Image Quality of Watermarked Images. (27th June 2010) - Iwata Iwata, Motoi Motoi; Kanaya Kanaya, Tomoo Tomoo; Shiozaki Shiozaki, Akira Akira; Ogihara Ogihara, Akio Akio
Abstract : We propose a digital watermarking method warranting the lower limit of the image quality of watermarked images. The proposed method controls the degradation of a watermarked image by using a lower limit image. The lower limit image means the image of the worst quality that users can permit. The proposed method accepts any lower limit image and does not require it at extraction. Therefore lower limit images can be decided flexibly. In this paper, we introduce 2-dimensional human visual MTF model as an example of obtaining lower limit images. Also we use JPEG-compressed images of quality 75% and 50% as lower limit images. We investigate the performance of the proposed method by experiments. Moreover we compare the proposed method using three types of lower limit images with the existing method in view of the tradeoff between PSNR and the robustness against JPEG compression.